Treatment of multidrug-resistant Klebsiella pneumoniae pneumonia in rats with the Wen Run Fei Ning formula: A preliminary study - Na Li; Jian Han; Yiwei Dong; Yanan Wang; Bing Ji; Fengxia Wang; Xinye An; Jiawen Ding (Journal of Vector Borne Diseases, 2023)
Background & objectives: To determine the effect of Wen Run Fei Ning formula (WRFNF) intervention in class I integron-mediated carbapenem-resistant Klebsiella pneumoniae. Methods: A drug-susceptibility test and PCR amplification were used to screen for carbapenem-resistant K. pneumoniae containing class I integrons. Following nasal drip and tail vein injection to infect healthy male rats with carbapenem-resistant K. pneumoniae, three models were created: control (group A); model (group B, tail vein injection); and model-WRFNF treatment group (group C, by tail vein injection). Rats in Group C were gavaged with pre-warmed WRFNF extract. On the third, fifth, and seventh days after the experiment, the rats in groups A and B were gavaged with an equal quantity of saline and killed in batches. Results: Group C showed considerably higher serum IL-6 and TNF- levels on days 3, 5, and 7 compared to group A, as well as a significant increase in peripheral blood leukocyte count and a histopathologic inflammatory cell infiltration of the lungs. As the WRFNF delivery duration was prolonged, group C's histopathologic inflammatory cell infiltration gradually improved in contrast to group B, with the biggest improvement occurring on day 7. Compared to group B, group C's serum IL-6 and TNF- levels were lower. When the trial's duration was increased to 7 days, the levels of IL-6 and TNF- in group C decreased on day 7 compared to on day 5. Interpretation & conclusion: WRFNF decreased inflammatory cell infiltration as well as IL-6 and TNF expression in the lung of the rats infected with carbapenem-resistant K. pneumoniae.